1977
DOI: 10.1021/bi00633a009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control and structure of glycolytic enzymes. 17. Pig liver phosphofructokinase: asymmetry properties, proof of rapid association-dissociation equilibriums, and effect of temperature and protein concentration on the equilibriums

Abstract: Sedimentation coefficient determinations show that, under comparable conditions, pig liver phosphofructokinase (PL-PFK) is larger than any previously studied phosphofructokinase; the molecular weight of PL-PFK at 4 °C at a protein concentration of 5 mg/mL is estimated to be greater than 10 000 000. Furthermore, the enzyme is very asymmetric as indicated by a strong concentration dependence of the sedimentation coefficient data and by a minimum intrinsic viscosity value at 20.0 °C of 30.8 cm3/g. Kinetic and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Brand and Soling (52) found a molecular weight for the rat liver enzyme of 365,000 using a linear gradient polyacrylamide gel electrophoresis in the presence of ATP. Massey and Deal (87,88) observed that the pig liver phosphofructokinase sediments as a single boundary, but, depending on protein concentration and temperature, its sedimentation coefficient varies from 44 to 104 S. The 104 S protein is the largest phosphofructokinase thus far reported and may correspond to a molecular weight of at least 10 million.…”
Section: B S T R U C T U~mentioning
confidence: 99%
See 2 more Smart Citations
“…Brand and Soling (52) found a molecular weight for the rat liver enzyme of 365,000 using a linear gradient polyacrylamide gel electrophoresis in the presence of ATP. Massey and Deal (87,88) observed that the pig liver phosphofructokinase sediments as a single boundary, but, depending on protein concentration and temperature, its sedimentation coefficient varies from 44 to 104 S. The 104 S protein is the largest phosphofructokinase thus far reported and may correspond to a molecular weight of at least 10 million.…”
Section: B S T R U C T U~mentioning
confidence: 99%
“…Preparation. Phosphofructokinase from livers of chicken (85), rat (52,86), and pigs (87) and from pig kidney (88) has been isolated in pure form, with specific activities ranging from 86 to 134 units/ mg. The chicken liver phosphofructokinase has been crystallized (85).…”
Section: B S T R U C T U~mentioning
confidence: 99%
See 1 more Smart Citation
“…PFK1 was recently identified as a filament-forming enzyme in Saccharomyces cerevisiae (Shen et al, 2016). Filament formation by PFK1 may be evolutionarily conserved because purified liver PFK1 (PFKL) forms asymmetric oligomers in vitro, as determined by gel chromatography (Kemp, 1971), sedimentation with analytical ultracentrifugation (Trujillo and Deal, 1977), fluorescence polarization (Reinhart and Lardy, 1980), and fluorescence correlation spectroscopy (Ranjit et al, 2014). However, only one previous study showed filamentous structures by transmission EM (TEM; Foe Despite abundant knowledge of the regulation and biochemistry of glycolytic enzymes, we have limited understanding on how they are spatially organized in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, binding of Pfk to intracellular proteins such as calmodulin (Marinho-Carvalho et al, 2006), actin (Liou & Anderson, 1980), microtubules (Vé rtessy et al, 1997) and caveolin 1 (Vallejo & Hardin, 2005) modulates the activity, oligomeric equilibrium and localization of Pfk within the cell. Moreover, the equilibrium between monomer, dimers, tetramers and higher oligomers affects Pfk activity (Trujillo & Deal, 1977;Luther et al, 1983). Mutations in the muscle Pfk gene can lead to type VII glycogen storage disease (Tarui disease; Toscano & Musumeci, 2007).…”
Section: Introductionmentioning
confidence: 99%